Exploration of Innovative Pedagogical Practices in Implementing an Independent Curriculum as a Manifestation of Independent Learning in The Diversity of Students - Herawan, Denisha Oktaviane; Herlambang, Yusuf Tri (Universitas Pendidikan Mandalika, 2025)
This study aims to identify and analyze innovative pedagogic practices that have emerged in response to the implementation of an independent curriculum in the context of Student Diversity, a curriculum that emphasizes teacher autonomy and student learning independence. This research uses qualitative approach with Case Study Method. Data collection techniques used in-depth interviews, participatory observation in class, Focus Group Discussion (FGD), and documentation analysis. Informants of this study were teachers and principals in a public elementary school in Sumedang, West Java. The data analysis technique used in this study is Miles and Huberman interactive model, which includes three main stages of data reduction, data presentation, and conclusion/verification. The results of this study indicate that high awareness among teachers of the importance of a strong foundation of pedagogic Science in implementing the Independent curriculum. This awareness encourages the creation of more integrated, collaborative, and student-centered learning, with a focus on developing each individual's unique potential. The study also identifies various examples of innovative pedagogic practices applied, such as differentiated learning to accommodate individual differences, project-based learning to increase relevance and engagement, and creative utilization of technology to enrich students learning experiences. The implications of the findings of this study indicate that teachers who have a high pedagogical awareness are able to design inclusive learning and responsive to student diversity. It is becoming an important foundation for the development of educational policies that support teacher autonomy and differentiated learning, as well as the strengthening of Teacher Learning Communities for the continuous improvement of professionalism.